2015
DOI: 10.1007/s11468-015-9986-2
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Broadband Asymmetric Polarization Conversion Due to Polarization-dependent Reflection

Abstract: We present the underlying theory, the design specifications, and the simulated demonstration of a high performance broadband asymmetric polarization conversion composed of an L-shaped gold particle and a gold nanoantenna array for the near-infrared regime. It can transform linearly polarized light to its cross polarization in the transmission mode for one propagation direction and efficiently reflect the light for the opposite propagation direction. The broadband asymmetric polarization conversion can be attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…A variety of bi-layer metasurfaces have been also reported to exhibit asymmetric transmission for linearly polarized incident light [105,106]. Further developments showed that bi-layer metasurface structures can be used to demonstrate increased bandwidth of the asymmetric transmission in the near infrared [107,108]. It was shown that the interlayer alignment could have very little effect on the asymmetric transmission [107], which indicates that the near-field coupling is negligible.…”
Section: Asymmetric Transmissionmentioning
confidence: 99%
“…A variety of bi-layer metasurfaces have been also reported to exhibit asymmetric transmission for linearly polarized incident light [105,106]. Further developments showed that bi-layer metasurface structures can be used to demonstrate increased bandwidth of the asymmetric transmission in the near infrared [107,108]. It was shown that the interlayer alignment could have very little effect on the asymmetric transmission [107], which indicates that the near-field coupling is negligible.…”
Section: Asymmetric Transmissionmentioning
confidence: 99%
“…However, the AT parameter is only 0.05 at d ¼ 150 nm, which could be attributed to the resonance of Fabry-Perot-like cavity; also, the interactions between the incident wave and the bi-layer omega-shaped metamaterial are all weak. 37,40 In addition, it was necessary to realize the AT effect experimentally,. Hence, in this study, we paid more attention on sample fabrications and AT measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The polarization state manipulation with metasurfaces always involves the tailoring of the anisotropic wave interference at the subwavelength scale. By manipulating the amplitude and phase of the electric or magnetic components in two orthogonal directions, the polarization state of light can be altered with structures occupying two orthogonal resonances, including elliptical nanoholes, L‐shaped nanoparticles, crossed nanodipoles . Among the abundant polarization devices, waveplates play a crucial and fundamental role in modern optical and photonic applications such as sensing, imaging, and communication.…”
Section: Single‐dimensional Manipulation Of Optical Waves With Metasumentioning
confidence: 99%